The Faroe-Shetland Connection : an architectural analysis of two side-by-side archipelagos - Jákup Nielsen 1996- (2023)
This thesis will focus on two side-by-side archipelagos in the North Atlantic Ocean, the Faroe Islands and Shetland, who share a similar origin. Political and societal factors, as well as culture and history, will be discussed with emphasis on how it has affected the architecture on the islands. The idea is to investigate how similar the building traditions used to be, and how similar, if similar at all, they are now, and why they are like that. We will start with explaining the cultural identity of the two nations – how and why do these peoples see themselves the way they do? Then we are going to lay out the political and societal circumstances relevant to shaping the building industry. The architectural characteristics of both archipelagos will be analyzed and compared with the cultural, political, and societal aspects in mind. The purpose of this thesis is to see how said factors can affect the architecture on the islands. These two archipelagos are picked in particular, because of their extreme similarities – and dissimilarities – they have to each other, which is what makes them unique.